1996
DOI: 10.2169/internalmedicine.35.529
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis and Therapy in Hepatitis C Virus-Associated Nephropathy.

Abstract: Weanalyzed the clinicopathological features and therapy in 19 patients with kidney disease accompanied by hepatitis C viral infection, including 12 patients with mesangial proliferative glomerulonephritis (including eight with IgA nephropathy), six with membranoproliferative glomerulonephritis (MPGN),and one with membranousnephropathy. Persistent hematuria and/ or proteinuria (10 patients) was the most commonfinding, followed by nephrotic syndrome (8 patients). Cryoglobulinemia was detected in six of 19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…Earlier introduction of interferon a and subsequent intensive immunosuppressive therapies including high-dose glucocorticoid, plasmapheresis, or immunosuppressive agents will likely achieve a better prognosis (4,7,10,20 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier introduction of interferon a and subsequent intensive immunosuppressive therapies including high-dose glucocorticoid, plasmapheresis, or immunosuppressive agents will likely achieve a better prognosis (4,7,10,20 …”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study, Dammacco et al [15] reported the use of corticosteroid therapy for type II mixed cryoglobulinemia. Komatsuda et al [16] reported that 5 of 11 patients treated with steroids showed improvement in renal impairment. In the present case, despite concerns about increased viral reproduction and risk of infection, corticosteroid therapy was administered for HCV-related glomerulonephritis to decrease cryoglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Review papers and case reports were excluded. Some manuscripts were excluded as they gave information on patients already reported in prior publications [10,11], others gave incomplete results [12,13,14,15,16,17,18]. …”
Section: Review Of the Literaturementioning
confidence: 99%